Cam Swing Linkage and Spring Linkage Combined Mechanism for Vehicle Side-door Latches with Electric Cinch and Release Priority Function - Yin Chuanshuo; Hang Lubin; Zhong Chuanlei; Qu Zhiyang; Zhang Jiale; Huang Xiaobo; Liu Zhe; Chen Yong (Jixie chuandong)
Aiming at the demand of electric cinch and release priority function of high-end vehicle door latches, a cam swing linkage and spring linkage combined mechanism is proposed, and a combined mechanism of double cam single swing linkage and spring four bar mechanism is constructed. Combined with the characteristics of limiting blocks, contact states, cam intermittent movement, profile abrupt change and other components, it can realize three motion modes of flexible and adaptive rolling, rigid pushing, avoiding and releasing, and switch among them. Embedded into the ratchet and pawl locking mechanism, the combined mechanism is transformed into electric cinch and release branches, corresponding to the three working conditions of the vehicle door latch: electric cinch, manual or power release and reset, and cinch branch reset. Based on the corresponding driving modes and motion boundary conditions, the compatible function of the cinch motion and the existing branches in the latch, the release priority function, and the half-lock release function in the case of the cinch pinch are studied and analyzed. The mechanism and the drive are embedded in the door latch for simulation, and the contact force between the release cam and the swing linkage, the swing linkage and the ratchet, and the ratchet and the paw are studied in all working conditions. The time of the mechanism to realize each function matches the design requirements of the vehicle door latch, the time of the electric cinch process is 420.97 ms, the reset time is 29.03 ms, and the manual release time is 622 ms.